2010
DOI: 10.12693/aphyspola.117.369
|View full text |Cite
|
Sign up to set email alerts
|

Optical Investigation of ZnO Nanowires

Abstract: In this study we report the application of synchrotron X-ray fluorescence, photoluminescence and Raman scattering techniques to the analysis of the incorporation of impurities in unintentionally doped ZnO nanowires. Highly ordered one-dimensional ZnO arrays were fabricated by an oxidation process of Zn metal electrodeposited in nanoporous anodic alumina template. X-ray fluorescence data show the contribution of residual elements into the ZnO nanowires growth. A rough analytical quantification of the main light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…Further, the membrane is characterized by Raman spectroscopy to examine the chemical composition of Cu nanowires, refer to Figure . The Raman characteristics of pure alumina membrane are already reported in literature . In comparison with the absence of bands in case of the pure alumina membrane, the Raman band centred at 1090 cm −1 in case of the membrane after electrodeposition confirmed the deposition of Cu inside alumina pores .…”
Section: Resultssupporting
confidence: 68%
“…Further, the membrane is characterized by Raman spectroscopy to examine the chemical composition of Cu nanowires, refer to Figure . The Raman characteristics of pure alumina membrane are already reported in literature . In comparison with the absence of bands in case of the pure alumina membrane, the Raman band centred at 1090 cm −1 in case of the membrane after electrodeposition confirmed the deposition of Cu inside alumina pores .…”
Section: Resultssupporting
confidence: 68%
“…Several publications were offered this year using XRF in conjunction with other techniques such as photoluminescence, Raman scattering or XRD for thin film characterisation. Martinez-Criado et al 521 reported the analysis of impurities in unintentionally doped ZnO nano-wires. Using the multi-element capability of XRF they determined the contribution of residual elements in the ZnO nano-wires growth.…”
Section: Thin Films Coatings and Nano-materialsmentioning
confidence: 99%